2020
DOI: 10.3389/fpsyg.2020.587129
|View full text |Cite|
|
Sign up to set email alerts
|

Gesture Influences Resolution of Ambiguous Statements of Neutral and Moral Preferences

Abstract: When faced with an ambiguous pronoun, comprehenders use both multimodal cues (e.g., gestures) and linguistic cues to identify the antecedent. While research has shown that gestures facilitate language comprehension, improve reference tracking, and influence the interpretation of ambiguous pronouns, literature on reference resolution suggests that a wide set of linguistic constraints influences the successful resolution of ambiguous pronouns and that linguistic cues are more powerful than some multimodal cues. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 44 publications
0
4
0
Order By: Relevance
“…They found that when speakers are asked to clarify the meaning of an ambiguous word used in the course of an extended discourse (in their work, homonyms), they are more likely to use a gesture in association with the problematic word; similar results were found by Holle and Gunter (2007). Similarly, when investigating the resolution of ambiguous statements related to neutral and moral preferences, Hinnell and Parrill (2020) showed that participants rely on gesture, when available, to understand the speaker's ambiguous statements. Particularly, gesture appeared to be used by observers to understand the speaker's opinion, since they were more likely to choose the idea accompanied by a gesture as the speaker's preference, regardless of whether the linguistic cue expressed a neutral idea or a moral view that might be considered socially unacceptable.…”
Section: Introductionmentioning
confidence: 77%
“…They found that when speakers are asked to clarify the meaning of an ambiguous word used in the course of an extended discourse (in their work, homonyms), they are more likely to use a gesture in association with the problematic word; similar results were found by Holle and Gunter (2007). Similarly, when investigating the resolution of ambiguous statements related to neutral and moral preferences, Hinnell and Parrill (2020) showed that participants rely on gesture, when available, to understand the speaker's ambiguous statements. Particularly, gesture appeared to be used by observers to understand the speaker's opinion, since they were more likely to choose the idea accompanied by a gesture as the speaker's preference, regardless of whether the linguistic cue expressed a neutral idea or a moral view that might be considered socially unacceptable.…”
Section: Introductionmentioning
confidence: 77%
“…More recently, scholars started to consider the ways in which gesture can impact the perception of abstract entities, such as arguments or conceptual ideas (Hinnell & Parrill, 2020; Parrill & Stec, 2017; Parrill et al., 2022). For example, Hinnell and Parrill (2020) presented participants with videos of speakers contrasting two ideas each accompanied by a gesture to the right or the left (e.g., “My little brother's not on Facebook because he thinks it's a waste of time” + gesture to right “but my other brother says he can't do job networking without it” + gesture to left). The speakers then expressed a preference or alignment with one of the ideas using an ambiguous pronoun (e.g., “I agree with him”).…”
Section: Studymentioning
confidence: 99%
“…However, many past studies have focused on how gestural input impacts addressees’ perception of concrete entities (e.g., where characters in a story were or how they acted), which already have physical spatial features that can map onto gesture. More recently, scholars started to consider the ways in which gesture can impact the perception of abstract entities, such as arguments or conceptual ideas (Hinnell & Parrill, 2020; Parrill & Stec, 2017; Parrill et al., 2022). For example, Hinnell and Parrill (2020) presented participants with videos of speakers contrasting two ideas each accompanied by a gesture to the right or the left (e.g., “My little brother's not on Facebook because he thinks it's a waste of time” + gesture to right “but my other brother says he can't do job networking without it” + gesture to left).…”
Section: Studymentioning
confidence: 99%
“…Co-speech gesture expressing the meaning of novel words can help children learn the words [170][171][172][173][174][175][176][177][178] . Furthermore, if gestures associate multiple referents at multiple locations, a subsequent gesture at one of the locations can disambiguate an ambiguous expression in speech [179][180][181] (also true for deictic co-sign gesture that accompanies pronouns 182 ).…”
Section: [H2] Information Receivedmentioning
confidence: 99%